Urban–rural disparities in maternal healthcare knowledge, attitudes, and practices among women with a recent live birth in Abuja and Gombe states, Nigeria - Chinelo Lynda Okoye; Precious Ojo Uahomo; Chinasa Godsgift Eni; Korfii Uebari; Chidi Emmanuel Ezerioha; Sussana Chinemerem Oguaba; Naomi Akpevwe Mogborukor; Umar Abubakar; Asemebo Goodness Okorosa; Oluwaseun Fadeyi (Frontiers in Public Health, 2026)
Background Nigeria bears the highest burden of maternal mortality globally, with marked urban–rural disparities. Rural women have significantly lower uptake of skilled antenatal care (60.7% vs. 91.8%) and facility-based delivery (48.5% vs. 81.3%). However, comparative data on maternal knowledge, attitudes, and practices (KAP) remain limited in northern Nigeria. This study compared maternal healthcare KAP between urban and rural women and identified predictors of good outcomes. Methods A community-based cross-sectional study was conducted in Abuja (urban) and Gombe State (rural) from June to July 2025. Women aged 15–49 years with a live birth in the preceding 12 months were included. Multi-stage stratified cluster sampling selected 1,218 women, yielding a final analytical sample of 1,045 (606 urban, 439 rural). A pre-tested interviewer-administered questionnaire assessed maternal knowledge (15 items, α = 0.84), attitudes (11 Likert items, α = 0.88), and practices (14 items, α = 0.81). Chi-square tests compared urban–rural differences. Hierarchical multivariable logistic regression, guided by the Social Ecological Model, identified predictors of good knowledge, positive attitude, and good practice, with variables entered in blocks according to SEM levels. Results Urban women had significantly higher proportions of good knowledge (66.3% vs. 25.5%, p < 0.001), positive attitudes (87.1% vs. 51.9%, p < 0.001), and good practices (57.8% vs. 23.9%, p < 0.001). Urban residence independently predicted good knowledge (AOR = 3.84, 95% CI: 2.67–5.53), positive attitude (AOR = 3.41, 95% CI: 2.38–4.89), and good practice (AOR = 2.84, 95% CI: 1.97–4.09). Secondary/tertiary education (AORs: 3.16, 2.11, 1.88) and higher income (AORs: 1.72, 1.54, 1.57) were consistent predictors. Good knowledge strongly predicted positive attitude (AOR = 4.28) and good practice (AOR = 3.91). Perceived affordability (knowledge AOR = 1.68; practice AOR = 1.81) and feeling safe at health facilities (knowledge AOR = 1.52; attitude AOR = 1.72) were significant predictors; respectful healthcare workers predicted attitude (AOR = 1.97) and practice (AOR = 1.69). Conclusion Substantial urban–rural gaps in maternal KAP persist, driven by education, income, and health system factors. Interventions that promote girls’ education, deliver targeted community health education, improve affordability and safety of maternal services, and strengthen respectful maternity care may reduce disparities in rural Nigeria.